Design of Multiband Patch Antenna for WLAN Applications - Ritisha V. Bhatt; G.D. Makwana (Science & Technology Asia, 2024)
This article proposes a compact slot-loaded multiband rectangular-shaped microstrip patch antenna. The proposed antenna of overall dimensions 30 × 30 × 1.56 mm3 radiates at 3.3 GHz, 5.8 GHz, 7.2 GHz, and 9.01 GHz to accommodate WiMAX and WLAN wireless applications. The antenna is mounted on Rogers AD255C substrate with the relative permittivity E𝑟=2.5 and loss tangent tan𝛿 < 0.002. The simulation results of return loss, gain, and bandwidth are examined for the proposed antenna. The proposed simple and low profile antenna offers simulated return loss of -19.40 dB, -12.76 dB, -27.57 dB, -31.62 dB, VSWR of 1.7, 1.2, 1.1, 1.4, and Gain of 5.25 dBi, 7.17 dBi, 5.09 dBi 6.06 dBi at resonant frequencies.